Performance Analysis of the Lebak Regency General Election Supervisory Agency (Bawaslu) Based on Law Number 7 of 2017 concerning General Elections in the 2024 Lebak Regency Regional Elections - Indrawati, Leni; Widodo, Cakra (MID Publisher International, 2024)
The regional head election is a tangible form of local democracy and political decentralization in Indonesia. The Election Supervisory Body (Bawaslu) plays a crucial role in ensuring fair, transparent, and accountable elections. This study aims to analyze the performance of Bawaslu Lebak Regency during the 2024 regional election based on Law No. 7 of 2017. The research uses a descriptive qualitative method with data obtained through observation, interviews, and documentation. The findings indicate that Bawaslu’s supervisory function still faces several challenges, including limited human resources, budget constraints, and low public participation. Moreover, various alleged violations such as money politics, vote inflation, and state apparatus involvement were not optimally addressed. The study concludes that while Bawaslu Lebak has carried out its supervisory duties in accordance with legal provisions, its effectiveness needs improvement through institutional strengthening, capacity building, and collaboration with civil society and relevant agencies.